Cognitive ability, character skills, and learning to play equilibrium: A level-k analysis - Gill, D; Prowse, V (University of Chicago Press, 2016)
We investigate how cognitive ability and character skills influence the evolution of play toward Nash equilibrium in repeated strategic interactions. We find that more cognitively able subjects choose numbers closer to equilibrium, earn more, and converge more frequently to equilibrium play. We estimate a structural model of learning based on level k reasoning and find a positive relationship between cognitive ability and levels. Furthermore, the average level of more cognitively able subjects responds positively to the cognitive ability of their opponents. More agreeable and emotionally stable subjects also learn faster, although the effect of cognitive ability is stronger than that of personality.